Peran Eddy dalam Distribusi Klorofil a di Selat Madura - Edwards Taufiqurrahman; Mochamad Furqon Azis Ismail, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Distribution of chlorophyll-a associated with Eddy circulation in the Strait of Madura.TheMadura Strait is an important area for fisheries due to nutrient rich water that may have triggering primary productivity of the strait and its surrounding. Information about seawater fertility of this area, particularly chlorophyll-a (Chl-a) as the indicator, are strongly needed. However, there are only few information about Chl-aconcentrations and seawater physical properties that may affect it forthe Madura Strait. The research on theChl-a content in the Madura Strait and its relation to the Eddy has been conducted in order to fill the gap of information about the Madura Strait fertility by using remote sensing and operational oceanography modelling. The deep basin under the Madura Strait creates Eddy within the water body of the Madura Strait, and this Eddy appears to affects the Chl-a distribution. In addition, the filaments seems to carry high-nutrient water from the coastto the offshore, leading to the enhancement of Chl-a content offshore of Madura Strait. Results of this study demonstrate the role of Eddy in distributing Chl-a in the Madura Strait.